Positive School and Classroom Environment: Precursors of Successful Implementation of Positive Youth Development Programs - Rachel C. F. Sun; Daniel T. L. Shek; Andrew M. H. Siu (The Scientific World Journal)
This case study was based on a school where the Tier 1 Program of the Project P.A.T.H.S. was integrated into the formal curriculum. In this case study, an interview with the school principal, vice-principal, and social worker was conducted in order to understand their perceptions of administrative arrangements and issues in the school, implementation characteristics, program effectiveness, program success, and overall impression. Results showed that several positive school and classroom attributes were conducive to program success, including positive school culture and belief in students' potentials, an inviting school environment, an encouraging classroom environment, high involvement of school administrative personnel, and systematic program arrangement.